Terms of Trade for Selected Crops in Rajasthan: Insights on Farmers’ Complex Crop Choice Behaviour (Indian Journal of Extension Education, 2022)
This study estimated the Terms of Trade (TOT) between the input and output prices for pearl millet, wheat, paddy and gram crops cultivated in Jaipur, Sri Ganganagar, Hanumangarh and Ajmer districts respectively in Rajasthan state for the period 1996-97 to 2018-19. It was found that the Compounded Annual Growth Rate (CAGR) of Procurement Price Index (PPI) and Farm Harvest Price Index (FHPI) have increased consistently for all crops with a CAGR ranging from 5-8 per cent p.a. The CAGR of Composite Input Price Index (CIPI) was always higher (ranging from 6-8% p.a.) than the PPI and FHPI indicating that the input prices have increased at a much higher rate than the output prices during the study period. Analysis revealed that TOT (ratio of PPI to CIPI and ratio of FHPI to CIPI) for all crops for most of the years was unfavourable (<100) as evident from negative CAGR (ranging from -0.15 to -2.40% p.a.). The selection of the base year in which output prices are around 150% (i.e. 1.5 times the cost of cultivation) of the composite input prices for estimating TOT is recommended. The study further explored as to why farmers cultivated these crops despite declining and negative TOT.